Full-Profile Pharmacokinetic Study of High Dose Baclofen in Subjects With Alcohol Use Disorder - Simon, Nicolas; Moirand, Romain; Dematteis, Maurice; Bordet, Régis; Deplanque, Dominique; Rolland, Benjamin (Frontiers in Psychiatry, 2018)
Baclofen a gamma amino-butyric acid type B (GABA-B) receptor agonist, which has raised some interest for the treatment of alcohol use disorder (AUD), occasionally at dose up to 300 mg/d. We conducted the first full-profile pharmacokinetic study on baclofen in AUD subjects, up to the oral daily dose of 300 mg. 60 subjects treated for AUD with marketed baclofen were enrolled in a prospective phase-1 study. Participants were divided into four dose groups (1: <60mg/d; 2: 60-120mg/d; 3: >120mg/d-180mg/d; and 4: >180mg/d), and they underwent a full-profile pharmacokinetic analysis of baclofen, using a nonlinear mixed effects modelling. The influence of different clinical and biological covariates was assessed in an upward modelling. 57 participants completed the study (522 observed concentrations collected). Racemic baclofen showed a linear pharmacokinetic profile, corresponding to a one-compartment model, with no influencing clinical or biological factor. The pharmacokinetic parameters of baclofen were (bootstrap 95% confidence intervals): absorption constant (Ka) 1.64 1/hr (1.34-2), clearance (Cl/F) 11.6 L/hr (10.8 – 12.3) and volume of distribution (Vd/F) 72.8 L (66.5–80.4) leading to a half-life of 4.4 h. The interindividual variability (IIV) was 44% (19-65), 21% (16-27) and 22% (11-36) for Ka, Cl/F and Vd/F, respectively. The residual variability was 24% (21-26). No serious adverse event was reported. Registration: EudraCT #2013-003412-46